2019
DOI: 10.1634/theoncologist.2019-0578
|View full text |Cite
|
Sign up to set email alerts
|

Novel Risk Scoring System for Patients with Metastatic Renal Cell Carcinoma Treated with Immune Checkpoint Inhibitors

Abstract: Background The International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) criteria are the gold standard for risk‐stratifying patients with metastatic renal cell cancer (mRCC). We developed a novel risk scoring system for patients with mRCC treated with immune checkpoint inhibitors (ICIs). Methods We performed a retrospective analysis of 100 ICI‐treated patients with mRCC at Winship Cancer Institute from 2015 to 2018. Several baseline variables were collected, including markers of inflammation, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 47 publications
(56 reference statements)
0
34
0
Order By: Relevance
“…Overall, three studies reported data on BMI among RCC patients receiving ICIs, and were all consistent in showing a positive association of BMI with survival outcomes [ 29 , 30 , 31 ]. The study by De Giorgi et al evaluated patients treated with nivolumab in the Italian Expanded Access Program (EAP) ( n = 313) [ 29 ].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Overall, three studies reported data on BMI among RCC patients receiving ICIs, and were all consistent in showing a positive association of BMI with survival outcomes [ 29 , 30 , 31 ]. The study by De Giorgi et al evaluated patients treated with nivolumab in the Italian Expanded Access Program (EAP) ( n = 313) [ 29 ].…”
Section: Resultsmentioning
confidence: 89%
“…The remaining 26 studies were subsequently reviewed and screened according to our inclusion and exclusion criteria. Finally, 18 studies were included in our systematic review ( Figure 2 ) [ 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The included studies were published between 2018 and 2020, and were retrospective studies, either single or multicenter; one study was a pooled analysis of patients treated with immunotherapy in the context of phase 2 and 3 trials.…”
Section: Resultsmentioning
confidence: 99%
“…In non–small cell lung cancer (NSCLC) patients treated with anti‐PD‐1/PD‐L1 antibodies, the ESPILoN score, which combines smoking history, liver metastasis, lactate dehydrogenase (LDH), and the NLR, was significantly correlated with PFS and OS 11 . In recurrent/metastatic renal cell carcinoma treated with anti‐PD‐1 antibodies, due to the Emory risk scoring system, which includes the monocyte‐to‐lymphocyte ratio (MLR), body mass index (BMI), and number of metastatic sites, patients in the very poor risk group had a significantly worse PFS and OS 12 . The Gustave Roussy Immune Score (GRIm‐Score) uses LDH, serum albumin, and the NLR and is reported to be significantly correlated with OS in patients who are administered anti‐PD‐1/PD‐L1 antibodies for NSCLC 13 .…”
Section: Discussionmentioning
confidence: 99%
“…BMI), and number of metastatic sites, patients in the very poor risk group had a significantly worse PFS and OS 12. The Gustave Roussy Immune Score (GRIm-Score) uses LDH, serum albumin, and the NLR and is reported to be significantly correlated with OS in patients who are administered anti-PD-1/PD-L1 antibodies for NSCLC 13.…”
mentioning
confidence: 99%
“…The development of biomarkers endowed with high sensitivity, specificity and accuracy able to identify which patients may truly benefit from the treatment with ICIs would allow to refine the therapeutic selection and to better tailor the treatment strategy. Furthermore, recent studies provided evidence that maybe even the prognostic stratification of mRCC patients should be refined in those treated with ICI, including the role of systemic inflammation besides the canonical criteria ( 74 ).…”
Section: Discussionmentioning
confidence: 99%